Kesiapan Masyarakat Dalam Program Penataan Akses Reforma Agraria di Desa Krikilan Kecamatan Kalijambe Kabupaten Sragen - Putri, Bahar Trianindha; Salim, M. Nazir; Pujiriyani, Dwi Wulan (Tunas Agraria, 2025)
The implementation of the Agrarian Reform Access Arrangement (PARA) program often faces a variety of responses from the community, ranging from support to rejection. The success of this program depends on the readiness of the community as the main subject in the implementation of the program. The purpose of this research is to analyze the level of community readiness in the implementation of the PARA program in Krikilan Village, Kalijambe District, Sragen Regency. The method used is a mixed-methods approach with the Community Readiness Model, which measures community readiness through five dimensions: community knowledge, leadership, community attitudes, community understanding, and local resources. The results of the study indicate that the leadership dimension has the highest score of 4.2, which is classified as a high level of ownership. Meanwhile, the community knowledge dimension has a score of 3.4, which is classified as a low level of awareness and falls into the lowest score category. The role and support of leaders in implementing the PARA program play an important role in increasing community readiness. The factors hindering community readiness in Krikilan Village include the fact that the community has not fully participated in the series of activities organized. This indicates that the level of community readiness in Krikilan Village has not yet reached its full potential.   Implementasi program Penataan Akses Reforma Agraria seringkali dihadapkan pada beragamnya respons masyarakat, mulai dari dukungan hingga penolakan. Keberhasilan program ini bergantung pada kesiapan masyarakat sebagai subjek utama dalam pelaksanaan program. Tujuan penelitian ini untuk menganalisis tingkat kesiapan masyarakat dalam pelaksanaan program PARA di Desa Krikilan, Kecamatan Kalijambe, Kabupaten Sragen. Metode yang digunakan adalah metode campuran dengan pendekatan Community Readiness Model, yang mengukur kesiapan masyarakat melalui lima dimensi yaitu pengetahuan masyarakat, kepemimpinan, sikap masyarakat, pemahaman masyarakat dan sumber daya lokal. Hasil penelitian menunjukkan bahwa dimensi kepemimpinan memiliki skor tertinggi yaitu sebesar 4,2 yang termasuk pada tingkat rasa kepemilikan yang tinggi. Sementara dimensi pengetahuan masyarakat memiliki skor 3,4 yang termasuk pada tingkat tidak ada kesadaran dan termasuk dalam kategori skor terendah. Peran dan dukungan pemimpin dalam melaksanakan program PARA memiliki peran penting untuk meningkatkan kesiapan masyarakat. Adapun faktor yang menghambat kesiapan masyarakat Desa Krikilan yakni masyarakat belum sepenuhnya terlibat dalam rangkaian kegiatan yang diadakan. Hal ini menunjukkan bahwa tingkat kesiapan masyarakat Desa Krikilan belum maksimal.